Animal pragmatism : rethinking human-nonhuman relationships - McKenna, Erin, 1965-; Light, Andrew, 1966- (Indiana University Press, 2004)
What does American pragmatism contribute to debates about human-animal relationships? These essays address concerns at the intersection of pragmatist philosophy and animal welfare. Covers moral consideration of animals, animal experimentation, institutional animal care, protection of animal habitat, farm animal welfare, and animal communication.